An evaluation of the effects of a training programme in Trauma Release Exercises on quality of life - McCann, Taryn (Department of Psychology, 2015)
This study investigated a unique body-based intervention, known as Trauma Releasing Exercises (TRE), which focuses on the neurophysiological residues of stress.